The effect of non-uniform combustion temperature profile on thermal fatigue cracking of an air-cooled gas turbine vane. (November 2019) - Yousefabad, Elham kamouri; Asadi, Saeed; Savadkouhi, Payam; Sedaghat, Omid; Bakhshi, Ali
Abstract: In this paper, Failure analysis report of a vane of a gas turbine made of nickel-base superalloy, with 16, 000 equivalent operation hours (EOH) of operation is presented. The investigation on the nozzle included activities like visual inspection, eddy current testing, chemical composition testing, microscopic examination and fractography. Visual and metallurgical examination of coating and base metal did not reveal any sign of microstructural degradation, creep deformation and hot corrosion. According to results obtained by visual inspection, fractographic and metallographic investigation, thermal fatigue or thermal shock mechanism was an active mechanism during failure of the nozzle. Computational fluid dynamics (CFD) and finite element method (FEM) analyses were carried out for this vane under different combustion conditions. For the cracked vane, strain pattern under different conditions was studied. Highlights: I explain root cause of thermal cracks by metallurgical, CFD and FEM analyses. High-temperature non-uniform combustion profile creates asymmetric temperature map. Asymmetric temperature map results in considerable amount of plastic deformation. The thermal fatigue or thermal shock cracking is due to plastic deformation. Metallurgical investigations have a good consistency with CFD and FEM results.